Monitored Anesthesia Care of Two Patients with Highly Elevated Subpulmonic Ventricular Pressure due to Adult Congenital Heart Disease - Tatsuya Kida; Tomoya Irie; Takahisa Goto (Case Reports in Cardiology)
Procedural sedation and analgesia for patients with adult congenital heart disease (ACHD) and highly elevated subpulmonic ventricular pressure require proper anesthesia care to prevent a pulmonary hypertensive crisis. We describe the monitored anesthesia care (MAC) of two patients with ACHD (a complete atrioventricular septal defect and congenitally corrected transposition of the great arteries) and highly elevated subpulmonic ventricular pressure. In both patients, preprocedural transthoracic echocardiography was useful for detecting severely elevated subpulmonic ventricular pressure. The MAC involved the infusion of propofol, dexmedetomidine, and fentanyl. Norepinephrine was continuously administered from the preanesthetic period. No hemodynamic instability or respiratory depression was observed during the MAC. Continuous administration of norepinephrine from the preinduction period was helpful for preventing hypotension. We added dexmedetomidine to our MAC regimen of propofol and fentanyl because it exerts both sedative and analgesic effects. Dexmedetomidine does not cause respiratory depression; thus, our MAC regimen is believed to be theoretically safe for patients with ACHD and elevated subpulmonic ventricular pressure. Our findings suggest that safe MAC for patients with ACHD and highly elevated subpulmonic ventricular pressure may require careful consideration of the anesthetic regimen and close observation by adequately trained personnel, which is best provided at regional ACHD centers.